LITERACY AND NUMERACY MENTORING PROGRAMS AND TEACHER PERFORMANCE IN ELEMENTARY SCHOOLS - Mursidati .; Syarwani Ahmad; Nur Ahyani (Jurnal Suluh Pendidikan, 2026)
This study examines the influence of literacy (X1) and numeracy (X2) mentoring programs on improving elementary school education quality, as reflected in Education Report Card indicators (Y) in Payaraman District, Ogan Ilir Regency. A quantitative explanatory approach with a correlational design was employed, involving 96 teachers selected purposively from a population of 209. A validated and highly reliable questionnaire (90 items) served as the instrument. Data analysis used descriptive statistics, prerequisite tests, and regression with SPSS 25. The results indicate that both literacy mentoring (R² = 0.465; p = 0.000) and numeracy mentoring (R² = 0.507; p = 0.000) significantly contribute to improving the Education Report Card, with numeracy showing a relatively larger contribution (56.6%). The study concludes that ongoing mentoring programs are effective in enhancing teacher competence and student learning outcomes. It recommends the Education Department continue the program with a focus on numeracy and low-achieving schools.